Growth and nutrient removal of three macrophytes in response to concentrations and ratios of N and P. Issue 7 (3rd July 2017) - Liao, JianXiong; Zhang, DeNan; Mallik, Azim; Huang, YuQing; He, ChengXin; Xu, GuangPing
ABSTRACT: Wastewater from different sources shows great differences in concentrations and ratios of N and P. In order to choose suitable plant species to remove excess N and/or P from polluted waters, it is important to know the performances of these plants under different N and P concentrations. In this study, we investigated the growth and N and P removal rate of three macrophytes, Coix lacryma-jobi, Iris wilsonii, and Arundo donax under six N and P combination treatments. C. lacryma-jobi preferred higher N and P concentrations (16 mg N L −1 and 3.2 mg P L −1 ), and increasing N supply could increase its P removal rate. I. wilsonii exhibited a growth preference at a combination of moderate N and P concentrations (8 mg N L −1 and 0.8 mg P L −1 ). A. donax could grow well at all combinations of N and P and had significantly higher relative growth rate and N and P removal rates than the other two species. These results showed A. donax is a promising species to treat various polluted waters and the other two species can be used specifically to treat certain types of wastewater.